Identification of sequences necessary for transcription in vitro from the Chlamydia trachomatis rRNA P1 promoter. - Tan, M (1996)
Chlamydia trachomatis RNA polymerase was partially purified by heparin-agarose chromatography and used in conjunction with a plasmid-borne G-less cassette template to characterize the C. trachomatis rRNA P1 promoter in vitro. Stepwise mutational analysis revealed that sequences in the -10, -25, and -35 regions are necessary for promoter activity, but no sequence upstream of position -40 is required. Partially purified C. trachomatis RNA polymerase and purified Escherichia coli holoenzyme exhibited some differences in promoter specificity.